2020
DOI: 10.1590/0001-3765202020200328
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Publication Profiles: Where and How Brazilian authors publish

Abstract: Publishing profi les can help institutions and fi nancing agencies understand the different needs of knowledge areas and regions for development within a country.Incites ® (Web of Science) was used to see where Brazilian authors were publishing, the impact, and the cost of this publishing. The USA was the country of choice for publishing journals, along with Brazil, England, and the Netherlands. While Brazilian authors continue to publish in hybrid journals, they are more often opting for closed access, with 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 33 publications
1
24
0
3
Order By: Relevance
“…PLoS One and Scientific Reports were the mega journals with the most published articles and highest APC values found in this research. Thus, our results delineate an internationalization of Brazilian research, a kind of research migration within scientific publication systems where peripheral countries as Brazil submit their best research to major commercial publishers and, in return, are required to pay high fees to access them (McManus et al 2020), confirming that there has been an increase in abroad Brazilian publications in all areas. Summarily, our results suggest that the creation of mega journals, a response from the editorial sector to the OA movement, created an opportunity for the scientific community from developing and middle-income countries to publish internationally.…”
Section: Minnitti Et Al (supporting
confidence: 63%
See 2 more Smart Citations
“…PLoS One and Scientific Reports were the mega journals with the most published articles and highest APC values found in this research. Thus, our results delineate an internationalization of Brazilian research, a kind of research migration within scientific publication systems where peripheral countries as Brazil submit their best research to major commercial publishers and, in return, are required to pay high fees to access them (McManus et al 2020), confirming that there has been an increase in abroad Brazilian publications in all areas. Summarily, our results suggest that the creation of mega journals, a response from the editorial sector to the OA movement, created an opportunity for the scientific community from developing and middle-income countries to publish internationally.…”
Section: Minnitti Et Al (supporting
confidence: 63%
“…Figure 7 presents an increase the total number of papers published in commercial and non-profit publishers from 2012 to 2019 (blue line), except for a decrease in 2016. According to McManus et al (2020), the drop in the number of articles in 2016 can be explained by three reasons: the global reaction to Plan S which made authors look for alternative journals to publish their works, the costs with APC and the lack of funding to cover them in Brazil, or the increase in postgraduate courses in Brazil without a budget increase. In fact, in 2015 and 2016 postgraduate courses lost 75% of the maintenance funding from CAPES, except for scholarships.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These fields are indeed those with the highest number of Brazilian scientists in the ranks. On the other hand, the impact of Brazilian research is lower for Social and Human Sciences (McManus et al 2020), which is confirmed by the low representation of Brazilians for these fields in the Ioannidis et al (2020) ranks. A recent analysis by Santiago et al (2020) showed significant disparities in the number of women holding a Ph.D. between areas in Brazil, with a predominance in the Humanities (19.8% of women Ph.D.), and a very small presence in Engineering (4.3%).…”
Section: Discussionmentioning
confidence: 93%
“…Brazilian women are underrepresented in all areas and are completely absent in some fields and subfields, even some that typically show high percentages of women, such as those related to Arts & Humanities (Barros & Mourão 2020). Brazil contributes with highly relevant research in several fields, such as in Medicine, Nursing, Physics & Astronomy and Dentistry (McManus et al 2020). These fields are indeed those with the highest number of Brazilian scientists in the ranks.…”
Section: Discussionmentioning
confidence: 99%